2004
DOI: 10.4049/jimmunol.173.11.6611
|View full text |Cite
|
Sign up to set email alerts
|

The Contraction Phase of Virus-Specific CD8+ T Cells Is Unaffected by a Pan-Caspase Inhibitor

Abstract: The effectiveness of protection conferred by CD8+ memory T cells is determined by both their quality and their quantity, which suggests that vaccine efficacy might be improved if it were possible to increase the size of the memory pool. Approximately 90% of virus-specific CD8+ T cells die during the contraction phase and, herein, we have attempted to increase the memory pool by reducing CD8+ T cell death. CD8+ T cell contraction has been attributed to apoptosis, or programmed cell death (PCD), which, classical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 74 publications
3
14
0
Order By: Relevance
“…Data from another study suggested that eVector T cell death can occur independent of mitochondrial cytochrome C activation of apaf-1 and the apoptosome [36]. Moreover, using a pan-caspase chemical inhibitor, one study suggested that T cell contraction is largely independent of caspase activation altogether, which is consistent with recent studies that indicate that cell death during thymic selection is independent of eVector caspases 3 and 7 [8,37]. Increased reactive oxygen species (ROS) may also predispose T cells to death and an inhibitor of ROS has been shown to increase the ex vivo survival of activated CD4 T cells [38].…”
Section: T Cell Contraction Independent Of Traditional Pathway Of Aposupporting
confidence: 72%
“…Data from another study suggested that eVector T cell death can occur independent of mitochondrial cytochrome C activation of apaf-1 and the apoptosome [36]. Moreover, using a pan-caspase chemical inhibitor, one study suggested that T cell contraction is largely independent of caspase activation altogether, which is consistent with recent studies that indicate that cell death during thymic selection is independent of eVector caspases 3 and 7 [8,37]. Increased reactive oxygen species (ROS) may also predispose T cells to death and an inhibitor of ROS has been shown to increase the ex vivo survival of activated CD4 T cells [38].…”
Section: T Cell Contraction Independent Of Traditional Pathway Of Aposupporting
confidence: 72%
“…Similarly, MC159 transgenic lymphocytes exhibited normal cell death markers, such as annexin V and TUNEL, during VV infection. These results are reminiscent of the lack of inhibition of CD8 ϩ T-cell death by pan-caspase inhibitors during VV infection (35). Although we cannot rule out the possibility that the transgenic lymphocytes could still undergo programmed necrosis, our results do indicate that the enhanced ␥␦ T-cell infiltration and innate immune control in MC159 transgenic mice during VV infection could not be attributed to inhibition of apoptosis.…”
Section: Discussionmentioning
confidence: 49%
“…This equal effect across all epitopes is different from chronic LCMV infection, where the number of NP396-404 specific T cells is affected to the greatest extent. How Bim facilitates the contraction process is unclear because treatment with caspase inhibitors does not block contraction of cells following LCMV infection (29).…”
Section: Ifn-␥-and Tnf-␣-producing Cells Increases In Cd8mentioning
confidence: 99%